The Influence of Capital Expenditure, Leverage, and Dividend Policy on the Relative Value of Non-Financial Companies Listed on the IDX - Vicky Vicky; Dewa Gede Wirama (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The research aims to analyze the impact of capital expenditure, leverage, and dividend policy on the relative value of non-financial companies listed on the Indonesia Stock Exchange. Using a quantitative method and multiple linear regression analysis, data were collected from the financial statements of companies over a certain period. Descriptive statistical tests, classical assumption tests, and hypothesis tests were conducted to analyze the data. The results indicate that capital expenditure and leverage do not have a significant impact on the relative value of the companies, while dividend policy has a positive and significant effect. These findings have important implications for investors in considering a company's dividend policy before making investments. For companies, the results serve as a reference to pay more attention to dividend policies in efforts to increase the relative value of the company.